Kursk 1943 : the greatest battle of the Second World War - Töppel, Roman (Modern military history, 2018)
The Battle of Kursk in the summer of 1943 was one of the greatest battles in military history involving more than 3 million soldiers, 10,000 tanks and 8,000 aircraft. While many books have been written on this allegedly most decisive battle of the Second World War, many legends live on, above all because of misleading information that recur in most publications - even in the most recent ones. Based on almost 20 years of research reassessing the primary sources, Roman Toeppel sheds light on the phase of decision-making, the preparations and the development of the battle in an engaging style that grips the reader's attention from the first page on. The author concentrates on little-known developments and events leading the reader to astonishing results. He also gives entirely new insights into the historiographic appraisal of this battle, putting thoroughly researched facts against erroneous popular beliefs, myths and legends that have been passed down among historians for generations.